Arthroscopic Thermal Shrinkage of Lunotriquetral Ligament Incomplete Tear without Triangular Fibrocartilage Complex Perforation - Kim, Byung Sung; Hwang, Jin Yeong; Kim, Sung Hwan; Park, Eunseok; Kim, Junyong (Journal of Wrist Surgery, 2024)
Background Few studies have reported the clinical results of arthroscopic debridement and thermal shrinkage for partial lunotriquetral (LT) ligament injury.Purpose We estimated the outcomes of arthroscopic thermal shrinkage of a traumatic LT ligament incomplete tear without triangular fibrocartilage complex (TFCC) perforation.Methods We evaluated the results of 24 patients. The mean follow-up was 16 months. Radiographs were examined for ulnar variance (UV) and radioulnar distance on a true lateral radiograph, and wrist function was assessed based on grip strength, Mayo wrist score, and Disabilities of the Arm, Shoulder, and Hand (DASH) score, both pre- and postoperatively.Results On preoperative magnetic resonance imaging (MRI), no obvious LT ligament tear was observed in any of the patients. The preoperative LT shear test was positive in 19 cases, while the LT ballottement test was positive in 18 cases and the ulnar stress test in 16 cases. Preoperatively, the average radiographic UV was 2.1 mm and the average radioulnar distance was 0.9 mm. The LT tear type was a flap tear in 22 cases and bucket handle tear in 2 cases arthroscopically. The visual analog pain scale score improved postoperatively (from 7.5 to 0.4). The average grip strength improved from 72.7% preoperatively to 89.8% postoperatively. The Mayo wrist score was excellent/good in 6/15 cases and fair in 3 cases, with the scores ranging from 68 to 87. The average DASH score improved from 36.8 to 7.Conclusion We should be careful to differentiate LT ligament tears from TFCC lesions in the cases with ulnar wrist pain, because LT ligament tears may not be detected by MRI. Arthroscopic thermal shrinkage for traumatic LT ligament tear can be an effective treatment.Level of Evidence Level IV.
Keywords: traumatic; triangular fibrocartilage complex tear; lunotriquetral ligament tear; arthroscopic debridement; thermal shrinkage